2018
DOI: 10.1002/cjp2.118
|View full text |Cite
|
Sign up to set email alerts
|

Breast cancer metastasis to gynaecological organs: a clinico‐pathological and molecular profiling study

Abstract: Breast cancer metastasis to gynaecological organs is an understudied pattern of tumour spread. We explored clinico‐pathological and molecular features of these metastases to better understand whether this pattern of dissemination is organotropic or a consequence of wider metastatic dissemination. Primary and metastatic tumours from 54 breast cancer patients with gynaecological metastases were analysed using immunohistochemistry, DNA copy‐number profiling, and targeted sequencing of 386 cancer‐related genes. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 65 publications
5
29
0
Order By: Relevance
“…Initial studies suggested that GATA3 is relatively sensitive and specific for tumors of breast or urothelial origin, and the downregulation of GATA3 has also been found to be associated with a poor prognosis of breast cancer. The significance of this transcription factor, especially for the inhibition of cancer cell metastasis, has been discussed in recent reports [22,23]. However, how does GATA3 participate in ccRCC development and metastasis is still unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Initial studies suggested that GATA3 is relatively sensitive and specific for tumors of breast or urothelial origin, and the downregulation of GATA3 has also been found to be associated with a poor prognosis of breast cancer. The significance of this transcription factor, especially for the inhibition of cancer cell metastasis, has been discussed in recent reports [22,23]. However, how does GATA3 participate in ccRCC development and metastasis is still unknown.…”
Section: Introductionmentioning
confidence: 99%
“…This study involved immunohistochemistry (IHC) analysis of: (1) a clinically annotated, consecutive series of primary breast tumours with >20 years follow up, herein referred to as the ‘general breast cancer cohort’ (described previously) 46 52 ; and (2) patient-matched pairs of primary and brain-metastatic breast tumours, herein referred to as the ‘brain-metastatic breast cancer cohort’ (br.MBC) ( Table 1 ). Both were sourced from the same diagnostic pathology centres in Queensland, Australia, and represent a similar patient population.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, there is a clear clonal ancestry during progression, and the early molecular drivers of behaviour and phenotype (e.g., mutations in TP53, PIK3CA, CDH1, GATA3, amplification of MYC, CCND1, ERRB2/HER2) remain prevalent drivers in metastatic deposits [71][72][73][74][76][77][78][79][80]. Despite this, significant intra-patient heterogeneity develops during progression, even in the absence of systemic therapy; this occurs to a greater extent in progression to distant metastases relative to local lymph nodes and is exacerbated by the selective pressures applied during adjuvant therapy [73,77,[81][82][83][84]. Changes in tumour phenotype or in the intrinsic molecular subtype during progression occurs in around 30% of patients (most often involving the down regulation of PR, but may also involve ER and less frequently a change in HER2 status) and may occur in a non-random manner at specific metastatic sites (e.g., lung, liver and bone metastases) [85][86][87][88].…”
Section: Genomics and Clonal Dynamic Changes During Metastatic Progrementioning
confidence: 99%
“…Changes in tumour phenotype or in the intrinsic molecular subtype during progression occurs in around 30% of patients (most often involving the down regulation of PR, but may also involve ER and less frequently a change in HER2 status) and may occur in a non-random manner at specific metastatic sites (e.g., lung, liver and bone metastases) [85][86][87][88]. To further complicate matters, the phenotype of different metastases within a patient can be heterogenous [83,86,[89][90][91][92].…”
Section: Genomics and Clonal Dynamic Changes During Metastatic Progrementioning
confidence: 99%
See 1 more Smart Citation